Some Non-standard Biparametric Poincaré Type Inequalities Through Harmonic Analysis - Cejas, María Eugenia (2022)
We show some non-standard Poincaré type estimates in the biparametric setting with appropriate weights. We will derive these results using variants from classical estimates exploiting the interplay between maximal functions and fractional integrals. We also provide a sharper result by using extrapolation techniques.